IDENTIFICATION OF PHYTOCOMPOUNDS FROM ARGEMONE MEXICANA AS INHIBITORS OF EPSTEIN-BARR NUCLEAR ANTIGEN TO COMBAT INFECTIOUS MONONUCLEOSIS - SHAFIQ K, MOHAMMED; HARISH, ROHIT (Innovare Journal of Medical Sciences, 2023)
Objectives: Mono or infectious mononucleosis (IM) is often referred to as the kissing illness. Epstein-Barr virus (EBV), which causes mono, is spread by saliva. Kissing, sharing a drink, or eating utensils with a person who has mononucleosis can transmit the disease to healthy individuals. This study investigates several bioactive compounds derived from plants to forecast how effective plant-based ligands will be at preventing IM. Methods: The purpose of the current study was to use computational techniques to assess the effectiveness of several phytochemicals against the EBV. The virtual screening tool PyRx was used to systematically perform molecular docking. The top 6 phytocompounds from Argemone mexicana were chosen among them to test their compatibility with the EBV nuclear antigen. Using ADMET filters, the ligands’ pharmacological evaluation was performed. Results: The phytocompounds Coptisine, Sanguinarine, and Dihydrosanguinarine from the plant A. mexicana were discovered to be the most potent antagonistic for the proteins EBV Nuclear Antigen 1 and EBV nuclear antigen 2. Conclusion: All of these bioactive chemicals could be considered of as deserving candidates for the suppression of IM due to their strong affinity for the protein. Among the top ligand, the phytoconstituent Coptisine demonstrated better binding with both targets.